Audit and account billing process in a private general hospital: a case study - Raquel Silva Bicalho Zunta; Antônio Fernandes Costa Lima (Universidade Federal de Goias, 2017)
Our study aimed to map, describe and, validate the audit, account billing and billing reports processes in a large, private general hospital.  An exploratory, descriptive, case report study. We conducted non-participatory observation moments in Internal Audit Sectors and  Billing Reports from the hospital, aiming to map the processes which were the study objects. The data obtained was validated by internal and external audit specialists in hospital bills. The described and illustrated processes in three flow-charts favor professionals to rationalize their activities and the time spent in hospital billing, avoiding or minimizing the occurrence of flaws and, generating more effective financial results. The mapping, the description and the audit validation process and billing and, the billing reports propitiated more visibility and legitimacy to actions developed by auditor nurses.